A Novel Electrophoretic Deposited Coordination Supramolecular Network Film for Detecting Phosphate and Biophosphate. Issue 32 (19th May 2017) - Chu, Tianshu; Zhang, Feng; Wang, Yi; Yang, Yangyi; Ng, Seik Weng
Abstract: A series of new lanthanide coordination supramolecular networks (CSNs) based on nalidixic acid (HNA) ligand were designed and synthesized. Their crystal structures were determined by single‐crystal XRD techniques. Thin films of these compounds were first successfully deposited on indium tin oxide (ITO) glass through one‐step electrophoretic deposition under mild conditions. The europium CSN film exhibits intense red emission and can act as a highly sensitive luminescent sensor for H2 PO4 − anions and adenosine triphosphate (ATP) in aqueous solution. The limits of detection of H2 PO4 − and ATP can achieve 0.68 and 1.9 μm respectively. The sensing mechanism was further explored through fluorescence and UV techniques. The fabricated sensor also showed excellent selectivity towards these phosphates in the presence of other coexisting ions (F −, Cl −, Br −, I −, SO4 −, CO3 2−, NO3 −, and AcO − ) without interference. Moreover, we demonstrated the feasibility of using this sensor to detect ATP in bovine serum samples, suggesting the potential value of application in real biosystems. Abstract : Film sensors : A series of new lanthanide coordination supramolecular networks (CSNs) based on nalidixic acid (HNA) ligand were designed and synthesized. These CSNs formed a luminescent film upon electrophoretic deposition (see figure) and the film exhibited excellent sensitivity and selectivity towards adenosine triphosphate (ATP).